2019
DOI: 10.1016/j.jtho.2019.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Spread Through Air Spaces (STAS) Is Prognostic in Atypical Carcinoid, Large Cell Neuroendocrine Carcinoma, and Small Cell Carcinoma of the Lung

Abstract: Introduction: Tumor spread through air spaces (STAS) has prognostic significance in lung adenocarcinoma and squamous cell carcinoma. We sought to investigate the prognostic importance of STAS in lung neuroendocrine tumors (NETs). Methods: All tumor slides from patients with resected pathologic stage I to III lung NETs (N ¼ 487) (299 with typical carcinoid [TC], 38 with atypical carcinoid [AC], 93 with large cell neuroendocrine carcinoma [LCNEC], and 57 with SCLC) treated between 1992 and 2012 were evaluated fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
64
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(65 citation statements)
references
References 35 publications
0
64
1
Order By: Relevance
“…Histological review showed that 26% of these patients had evidence of STAS, which was associated with distant metastasis, higher CIR and lung cancer-specific cumulative incidence of death overall (independently of histological subtype). 13 In fact, in patients with LCNEC and SCNEC, STAS was found to be an independent poor prognostic factor.…”
Section: Evolution Of the Concept Of Stas In Adenocarcinomamentioning
confidence: 95%
“…Histological review showed that 26% of these patients had evidence of STAS, which was associated with distant metastasis, higher CIR and lung cancer-specific cumulative incidence of death overall (independently of histological subtype). 13 In fact, in patients with LCNEC and SCNEC, STAS was found to be an independent poor prognostic factor.…”
Section: Evolution Of the Concept Of Stas In Adenocarcinomamentioning
confidence: 95%
“…In another report, however, STAS was found to impact the cumulative incidence of recurrence (CIR) and to be an independent risk factor for lung cancerspecific cumulative incidence of death (LC-CID) in SCLC. 9 In large cell neuroendocrine carcinoma, the incidence of STAS was reported to be 43.0%, and STAS was also found to be an independent risk factor for CIR and LC-CID. In typical carcinoid, the incidence of STAS was from 16.0% to 20.5%, while in atypical carcinoid, this incidence was from 37.0% to 48.0%.…”
Section: Clinicopathologic Features and Prognosis Of Stasmentioning
confidence: 97%
“…1 STAS is defined as tumor cells within air spaces in the lung parenchyma beyond the edge of the main tumor. STAS was initially observed in adenocarcinomas (ADC) ( Figure 1A and B); however, with recent in-depth studies, STAS was identified in other types of lung cancer including squamous cell carcinoma (SQCC) ( Figure 1C and D), [2][3][4] pleomorphic carcinoma, 5 invasive mucinous adenocarcinoma (IMA) ( Figure 1E and F), 6,7 neuroendocrine tumors 8,9 and lymphoepithelioma-like carcinoma. 10 To date, several articles have reviewed the studies concerning the significance of STAS; [11][12][13] however, most of these articles focused on the correlation between STAS and clinicopathologic features or prognosis, and few articles summarized the significance of STAS on other aspects.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Regarding the definition of STAS, STAS is a novel pathologic feature in lung cancer that includes three histomorphological characteristics: solid nests, micropapillary patterns and single cells . STAS is also associated with recurrence and survival in squamous cell carcinoma, lung large cell neuroendocrine carcinoma, and lung small cell carcinoma, even lung pleomorphic carcinoma . STAS has been reported to be related with an aggressive tumor behavior, such as a larger tumor size, a high pathologic stage, lymphatic or vascular invasion, pleural invasion, tumor budding and increased micropapillary or solid structures in lung adenocarcinomas .…”
Section: Discussionmentioning
confidence: 99%